(untitled) (Journal of the College of Basic Education, 2022)
Iraq is characterized by an important location linking trade routes between East and West, which led to occupy the main position in the trade because it has land roads that represent the artery that passes through many countries through which trade convoys. Nature provided the ancient Iraqis with good routes for their commercial mobility. The research problem is: What is the importance of the land routes in Iraq in the past and whether they differed before and after Islam, whether they are (internal or external), as well as what are the most important factors affecting the emergence and development of routes in Iraq and have contributed to the development of trade in Iraq ? The research aims at shedding light on the land routes in Iraq as the topic is important and suffers from the fact that it has not been previously addressed in specialized studies, although it is mentioned implicitly, so this research sheds light on this aspect of transport and its relevance to Iraq’s trade. We conclude that the road used by the population linking Iraq to neighboring regions and was extending in different directions inside and outside Iraq, as the roads extended the mountainous areas in the northern sides were rugged, but they were sometimes used in the conduct of commercial convoys. The roads leading to the eastern provinces stretched with the mountains of Zakros, making it easy to travel to neighboring areas. Finally, the roads leading to the western regions appear to have been active and multiple due to the presence of valleys along their roads and linking Iraq to the Levant and the Mediterranean coast.